Indications for microsurgical reconstruction of congenital hand anomalies by toe-to-hand transfers - Jones, Neil F. (Springer US, 2013)
BACKGROUND: The indications for microsurgical toe-to-hand transfers in congenital hand surgery have not been defined as clearly as for posttraumatic reconstruction of thumb and finger amputations. The purpose of this study was to develop simple guidelines for referral of children with congenital absent digits for consideration of microsurgical reconstruction with toe-to-hand transfers, based on the morphological or radiographic anatomy of the hand anomaly, not on embryological classifications. METHODS: From a consecutive series of 204 children referred with congenital absence of the thumb and fingers, 100 toe-to-hand transfers were performed. The indications for microsurgical reconstruction of these children were analyzed retrospectively. RESULTS: Forty-one thumbs were reconstructed in 38 children—15 children with an absent thumb distal to the metacarpal base but with four relatively normal fingers; 12 children with an absent thumb and only one or two digits remaining on the ulnar side of the hand; and 11 children with complete absence of all five digits. Twenty-nine second toes and 12 great toes were transferred to reconstruct congenital absent thumbs. Fifty-nine fingers in 52 children were reconstructed mostly with single second toe transfers—41 children with a thumb but absence of all four fingers and 11 children with absence of all five digits. CONCLUSIONS: The morphological or radiographic anatomy of a child’s hand with congenital absent digits is a more logical indication for microsurgical reconstruction than any embryological classification. The three most common indications for toe transfers for reconstruction of congenital absent thumbs are (1) absent thumb distal to the carpometacarpal joint with four relatively normal fingers, (2) absent thumb with only one or two fingers remaining on the ulnar border of the hand, and (3) complete absence of the thumb and all four fingers. The two indications for toe transfers for reconstruction of congenital absent fingers are (1) absence of all four fingers but with a normal thumb remaining and (2) complete absence of all five digits.